The Routledge Handbook of Emotions in the Ancient Near East - Sonik, Karen 19XX-; Steinert, Ulrike (Taylor & Francis, 2023)
Affection; Akkadian; Ancient; Archaeology; Art; Brotherhood; Civilizations; East; Emotions; Expression; Feeling; History; Hittite; Kings; Kingship; Materialization; Mesopotamia; Remains; State; Texts; Theoretical; Translating; Transliteration; Visual